"Optimizing Pharmaceutical Formulations: Advancements in Nanosuspension Pre-Formulation to Enhance Solubility and Bioavailability of Active Agents" - Bhosale, Pramod Motiram; Singh, Manmeet (International Journal of Membrane Science and Technology, 2023)
This study aimed to enhance the bioavailability of a poorly water soluble drug by developing a nanosuspension through an innovative formulation method. The nanosuspension was produced with meticulous attention to the materials reliability and excellent quality. Nepafenac was characterised in the pre-formulation study by establishing its melting point, solubility in different solvents, organoleptic properties, and creating a calibration curve. We utilised UV spectroscopy to determine the maximum wavelength (?max) of Nepafenac and construct a standard calibration curve in ethanol. To ensure the compatibility of the medicine with the polymers (Pluronic F127 and HPMC E 5), Fourier Transform Infrared Spectroscopy (FTIR) was utilised for drug interaction analysis. The nanosuspension was produced using the solvent diffusion approach. The effect of different concentrations of Poloxamer 407 and HPMC E 5 on the formulation's effectiveness was investigated experimentally using a 32 complete factorial design. We used Response Surface Methodology (RSM) and statistical analysis to enhance the formulation concerning in vitro release, particle size, and viscosity. The pre-formulation characteristics of Nepafenac met the standards outlined in the Pharmacopoeial regulations. The maximum absorption wavelength (?max) of Nepafenac was confirmed by UV spectroscopy, and a reliable calibration curve was created. The FTIR analysis showed no chemical interaction between the medicine and polymers. RSM and experimental design indicated that Poloxamer 407 and HPMC E 5 had a substantial impact on the performance of the nanosuspension. Analysis of variance (ANOVA) confirmed the model and parameters that influence controlled drug release percentage, particle size, and viscosity. Optimal conditions for enhancing drug delivery and reducing particle size were determined by the analysis of contour and response surface plots. The optimal parameter values, as indicated in the desirability plots, closely matched the anticipated values. The experimentation confirmed the viability and effectiveness of the nanosuspension formulation generated based on the RSM findings.